Knowledge gaps and socio-demographic disparities in dengue awareness among high-risk communities in Tanzania: a cross-sectional study - Clement N. Mweya (BMC Public Health)
Abstract Background Community knowledge plays a crucial role in preventing dengue outbreaks. This study assessed dengue fever awareness and knowledge gaps among Tanzanians to inform prevention efforts. Methods A cross-sectional community-based study was conducted from April to June 2022 across Kyela, Bahi and Ngorongoro districts. Data on socio-demographics, dengue knowledge, transmission, symptoms and prevention were collected using questionnaires from 482 participants aged ≥ 18 years. Descriptive statistics, χ2 and logistic regression analysis examined knowledge levels in relation to socio-demographic factors. Results A majority of participants (76.6%) reported prior knowledge of dengue fever. Awareness of mosquito bites as a transmission mode was relatively high (68.8%), but specific knowledge of Aedes mosquitoes as vectors was significantly lower at only 23.4% (χ2 = 132.50, P < 0.05). Findings indicated a fair knowledge of vector biting frequency (52.5%) and breeding sites (57.9%). However, most demonstrated good knowledge of symptoms (52.3%) and prevention (66.4%). Knowledge levels differed across demographic groups. For instance, women were less likely than men to report knowledge of vector bite frequency (AOR 0.41, 95% CI 0.22–0.76). Conclusions There are critical dengue knowledge gaps among communities at high epidemic risk regarding vectors, transmission dynamics and breeding ecology. Targeted educational interventions considering disparities across socio-demographics are urgently required to raise awareness, improve participation in integrated control programs and empower at-risk populations to mitigate outbreaks.